The predictors of COVID-19 mortality among health systems parameters: an ecological study across 203 countries - Sutapa Bandyopadhyay Neogi; Shivam Pandey; G. S. Preetha; Sumant Swain (BMC, 2022)
Key messages Health financing parameters are better predictors of cumulative COVID-19 cases and deaths per million population compared to other health systems and global health security indicators. More robust and valid indicators are required to assess the performance of health system.